FREQUENCIES OF DIFFERENT PERIPHERAL NERVOUS SYSTEM PATHOLOGIES AMONG CASES OF LUMBAR RADICULAR PAIN USING ELECTRODIAGNOSTIC STUDIES: Lumbar Radicular Pain - Ayaz, Saeed Bin; Waheed, Akhtar; Ali, Liaqat (Pakistan Armed Forces Medical Journal, 2014)
Objective: To discover the spectrum of diagnoses on nerve conduction studies/Electromyography in patients with lumbar radicular pain, test preponderance of the commonest pathology and correlate commonest pathology with age ≥ 50 years, gender and unilateral or bilateral involvement.Study Design: A descriptive cross-sectional study of 539 patients.Place and Duration of the Study: The department of Electrodiagnostic Studies, Armed Forces Institute of Rehabilitation Medicine, Rawalpindi from January 2012 to December 2012.Material and Methods: Using non-probability consecutive sampling 539 patients referred with complaints of lumbar radicular pain were subjected to electrodiagnostic evaluation for presence of lumbosacral radiculopathy, polyneuropathy, sciatic nerve injury or a combination of these. The preponderance of commonest pathology was tested statistically. The frequencies were then related statistically to age ≥ 50 years, gender and unilateral or bilateral involvement.Results: A total of 539 patients (age: 18- 85 years) were registered. 355 (66%) were males and 261 (48.4%) patients were ≥ 50 years. Nerve conduction studies/Electromyography findings were abnormal in 386 (77.6%) patients. The commonest diagnosis was lumbosacral radiculopathy in 65% followed by polyneuropathy with superimposed lumbosacral radiculopathy in 7%. The preponderance of lumbosacral radiculopathy was statistically found significant (p < 0.05) and it was common in individuals ≥ 50 years.Conclusion: Lumbosacral radiculopathy is highly expected to be found on nerve conduction studies / electromyography in patients who present with lumbar radicular pain. The lumbosacral radiculopathy is more common in individuals of age 50 years and above.